2013
DOI: 10.1088/0953-2048/26/4/045010
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the superconducting properties of NbN thin film on single-crystal silicon substrate by using a TiN buffer layer

Abstract: Thin superconducting NbN film on silicon substrate is a promising material for use in some ultrasensitive sensors and detectors, such as the hot-electron bolometer mixer and the superconducting nanowire single-photon detector. Due to the large mismatch between NbN film and Si substrate, the NbN film has a lower critical temperature than NbN film on MgO substrate. TiN has been experimentally verified as a good buffer layer due to having the same face-centered-cubic crystallite structure as and a lattice constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…We find that the resistivity ratio, which is smaller than 1, decreases almost linearly from 0.98 to 0.89 as N 2 flow rate is increased from 1.4 sccm to 2.9 sccm. This kind of temperature dependence is commonly observed in polycrystalline NbN films [1][2][3][4][5][6][7][8][9] and often interpreted as grain-boundary scattering effect [3,4]. T c and normal state resistivity for all the NbN thin films studied in this work are summarized in Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…We find that the resistivity ratio, which is smaller than 1, decreases almost linearly from 0.98 to 0.89 as N 2 flow rate is increased from 1.4 sccm to 2.9 sccm. This kind of temperature dependence is commonly observed in polycrystalline NbN films [1][2][3][4][5][6][7][8][9] and often interpreted as grain-boundary scattering effect [3,4]. T c and normal state resistivity for all the NbN thin films studied in this work are summarized in Fig.…”
Section: Resultssupporting
confidence: 53%
“…To obtain a high T c and a low normal-state resistivity, substrates such as single-crystalline MgO [7] and Al 2 O 3 [8], which have low lattice mismatch with NbN, have been used for the epitaxial growth. In the case of using Si as substrates, buffer layer of TiN or Al 2 O 3 was used to reduce large lattice mismatch between Si and NbN [9]. Our purpose for preparation of NbN thin film is to use it in a spin-switch device as a passive superconducting layer sandwiched between two ferromagnetic layers.…”
Section: Introductionmentioning
confidence: 99%
“…Various thin films such as MgO, AlN, and TiN have been used as the buffer layers for the epitaxial growth of NbN films. [20][21][22][23] Among these, TiN is a promising material to be used as the buffer layer because TiN and NbN have the same crystal structure with a lattice mismatch of only 3.5%. Recently, we fabricated (200)-oriented TiN films on Si (100) substrates using DC magnetron sputtering and showed that TiN films deposited at high temperature exhibit highly crystalline structures and good superconducting properties.…”
mentioning
confidence: 99%
“…A clear trend of decreasing Tc for decreasing thickness is observed. The suppression of Tc has been studied by many groups and it has been assigned to the proximity effect, which occurs when a superconducting material is in contact with a non-superconducting layer [27,[34][35][36]. This effect was studied in Ref.…”
Section: A Optimization Of the Film Depositionmentioning
confidence: 99%